Relationship of the level of self-esteem and injuries in young sambists - Shumova, N. S.; Cuj, C. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the relationship between the level of self-esteem and other psychological factors with the severity and frequency of injuries among sambo wrestlers aged 18-25 years.